PENGARUH PENGGANTIAN TEPUNG IKAN DENGAN TEPUNG MAGGOT (Hermetia illucens) DALAM RANSUM TERHADAP PERFORMANS BROILER - Dengah, Sandy P; Umboh, J F; Rahasia, C. A.; Kowel, Y H.S (Universitas Sam Ratulangi, 2016)
ABSTRACT EFFECT OF SUBSTITUTION OF FISH MEAL WITH MAGGOT (Hermetia illucens) IN THE DIETS ON BROILER CHICKEN PERFORMANCE. Maggots (maggot meal) have been widely studied as a good alternative to fish meal in broiler chicken and pigs. The present study was designed to elaborate the effect of substituting fish meal with maggot (Hermetia illucens) meal in the diets on feed efficiency of broiler chicken. Eighty day old chicks (DOC) broiler chicks were placed in battery cages and were assigned to each dietary treatment (5 treatments) which was replicated four times in a completely randomized design (CRD) arrangement anddatawere all submitted to the ANOVA procedure. Differences were considered significant at P< 0.05.Â Diets were formulated to meet or exceed starter and finisher broiler requirements as recommended by NRC (1994). Treatment diets were formulated as follow: R0 =Â 100.0% fish meal (15.0% in the diet) + 0% maggot meal (0% in the diet); R1 =Â 75% fish meal (11.25% in the diet) + 25.0% maggot meal (3.75% in the diet); R2 = 50.0% fish meal (7.5% in the diet) + 50.0% maggot meal (7.5% in the diet); R3 = 25.0% fish meal (3.75% in the diet) + 75.0% maggot meal (11.25% in the diet); and R4 = 0% fish meal (0% in the diet) +100.0% maggot meal (15.0% in the diet). Parameters measured were: feed consumption, daily gain, and feed efficiency ratio. Research results showed that feed consumption, daily gain, and feed efficiency ratio of starter and finisher broiler chicks in the present study were significantly decreased as maggot meal substituted fish meal at the level of 100% or 15.0% in the diet (R4). It can be concluded that maggot (Hermetia illucens) mealcould replace fish meal up to 75.0% or 11,25% in the diet without any negative effects on feed efficiency ratio of broiler chicken. Keywords: Fish meal, Maggot (Hermetia illucens) meal, Broiler chicken, Feed efficiency ratio